Biorefining Brazilian Green Propolis: An Eco-Friendly Approach Based on a Sequential High-Pressure Extraction for Recovering High-Added-Value Compounds - Guilherme Dallarmi Sorita; Wilson Daniel Caicedo Chacon; Monique Martins Strieder; Camilo Rodriguez-García; Alcilene Monteiro Fritz; Silvani Verruck; Germán Ayala Valencia; José A. Mendiola (Molecules)
Propolis is a valuable natural resource for extracting various beneficial compounds. This study explores a sustainable extraction approach for Brazilian green propolis. First, supercritical fluid extraction (SFE) process parameters were optimized (co-solvent: 21.11% v/v CPME, and temperature: 60 °C) to maximize yield, total phenolic content (TPC), antioxidant capacity, and LOX (lipoxygenase) inhibitory activity. GC–MS analysis identified 40 metabolites in SFE extracts, including fatty acids, terpenoids, phenolics, and sterols. After selecting the optimum SFE process parameters, a sequential high-pressure extraction (HPE) approach was developed, comprising SFE, pressurized liquid extraction (PLE) with EtOH/H2O, and subcritical water extraction (SWE). This process was compared to a similar sequential extraction using low-pressure extractions (LPE) with a Soxhlet extractor. The HPE process achieved a significantly higher overall yield (80.86%) than LPE (71.43%). SFE showed higher selectivity, resulting in a lower carbohydrate content in the non-polar fraction, and PLE extracted nearly twice the protein amount of LPE–2. Despite the HPE selectivity, LPE extracts exhibited better acetylcholinesterase (AChE), butyrylcholinesterase (BChE), and LOX inhibition, demonstrating that the neuroprotective and anti-inflammatory activity of the extracts may be associated with a symbiosis of a set of compounds. Finally, a comprehensive greenness assessment revealed that the HPE process proved more sustainable and aligned with green chemistry principles than the LPE method.